Daughters of Zelophehad – Quest for gender justice in land acquisition and ownership - Resane, Kelebogile T. (HTS teologiese studies, 2021)
This article studies the resilience of five daughters of Zelophehad in requesting to be allocated the land as their father never had a son. The Mosaic law discriminates women against land allotment or ownership. However, the same law teaches that only God owns the land and the occupants are the custodians. Deuteronomic tradition presents land custodianship as a right dispensed solely at the discretion of the owner, while Leviticus presents land as a resource to be properly managed by the recipients for sustainability. Exodus presents land occupation as a social concern. The patriarchal views of marginalising women from owning the land are challenged by the spirit of the daughters of Zelophehad who challenged the ancient traditional biblical laws with their patriarchal endorsements that restricted them to land ownership.Contribution: Many African societies are still patriarchal, marginalising women from land ownership and occupation. Women in these traditional societies are encouraged to welcome and embrace the spirit of the daughters of Zelophehad by embracing justice education that promotes equality and social justice. They should boldly appear before the authorities to define their marginalisation regarding land possession and ownership. They can enhance their participation in economic growth by taking the risks and forming the strong networks that lead to viable economic partnerships and corporations.